Sula - Morrison, Toni (Vintage, 1998)
As girls, Nel and Sula shared each other's discoveries and dreams in the poor black mid-West of their childhood. Then Sula ran away to live her dreams and Nel got married. Ten years later Sula returns and no one, least of all Nel, trusts her.